Disrupted Coherence Between Upwelling Strength and Redox Conditions Reflects Source Water Change in Santa Barbara Basin During the 20th Century. Issue 12 (21st December 2021) - Alfken, Susanne; Wörmer, Lars; Lipp, Julius S.; Napier, Tiffany; Elvert, Marcus; Wendt, Jenny; Schimmelmann, Arndt; Hinrichs, Kai‐Uwe
Abstract: Varved sediments from the center of the Santa Barbara Basin (SBB) off southern California are a valuable archive for high‐resolution climate reconstruction. Using mass spectrometry imaging of lipid biomarkers, this study examines interactions of perennial upwelling strength and oxygen‐driven redox conditions at the sediment‐water interface from 1900 CE to 2009. In the SBB, variations in upwelling are recorded by isoprenoidal tetraethers from planktonic archaea, while the redox‐sensitive C29 stanol/stenol ratio reflects oxygen content in the bottom water and surficial sediment. The changing coherence of these two proxies allows investigation of the interplay between upwelling, bioproductivity and redox conditions, and their dependence on SBB source water composition during the 20th century. Prior to a large‐scale oceanographic regime shift observed in the North Pacific in the 1970s, both proxies are positively correlated: periods of enhanced upwelling promoted mixing, resulting in increased oxygen availability at the sediment‐water interface; conversely periods of reduced upwelling favored development of oxygen‐depleted water at depth. In the wake of the basin‐wide regime shift, changing oceanographic conditions led to a reduction in the southward flowing California Current and a stronger influence of the poleward California Undercurrent, which increased stratification and the supply of warm, oxygen‐poor tropical water in the subsurface. As a result, oxygen availability in SBB bottom waters was predominantly regulated by upwelling‐induced productivity and subsequent oxygen‐consuming remineralization of organic matter. Plain Language Summary: Changes in the oceanographic conditions of the southern California Current System (CCS) have a strong influence on the marine ecosystem. Molecular fossils from marine plankton preserved in Santa Barbara Basin sediments provide a record of these past changes. In this study, we deciphered this record using a laser‐based detection of these molecular fossils that results in subannually resolved information on upwelling of nutrient‐rich water and redox conditions in bottom waters for the past century. The resulting data set reflects the interplay of these oceanographic factors in response to regional climatic changes in the North Pacific. Up to the 1970s, the upwelling signal and oxygen availability behave in synchrony, but thereafter this relationship reverses. This switch in the 1970s coincides with a regime change throughout the North Pacific that greatly altered oceanographic conditions in the southern CCS. Subsequently, the influence of warm and low‐oxygen waters from the tropics has greatly increased, resulting in warming and greater stratification of the water column. While upwelling could cause a mixing effect of bottom waters prior to this regime change, this effect is now limited and oxygen availability is additionally reduced due to oxygen‐consuming degradation of organic material. Key Points: Algal sterols and archeal tetraether lipids are used to track redox conditions and upwelling strength with subannual resolution Prior to the 1970s regime shift, upwelling amplified mixing, resulting in increased oxygen availability at the sediment‐water interface Thereafter, altered source water in this region resulted in lowered upwelling intensity and biogeochemical control of oxygen availability